Analysis of Economic Potential of Lebak Indonesia Regency Based on Leading Sector - Puspita, Mutiara Eka; Handayani, Aniek Sri; Ratnawati, Ratnawati; Medtry, Medtry (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Lebak Regency has the largest area in Banten Province, Indonesia with an area of 3426.56 km or 35.46% of the total area of Banten province. With this landscape, Lebak has development potential which is indicated by the existence of national strategic projects such as the construction of the Serang-Panimbang toll road, the construction of the Karian dam which is the third largest in Indonesia and the development of the new city of Maja. The realization of investment in Lebak Regency for 2 consecutive years in 2019 and 2020 has always been above the target. This is inseparable from the strong commitment of the Lebak Regency Government to improve a conducive investment climate. An analysis of the economic potential is needed to determine the comparative advantage of the location so that the promotion strategy to bring in investment can run effectively. From the results of the comparison of the Gross Regional Domestic Product (GRDP) of Lebak Regency with the Provincial Gross Regional Domestic Product, it was found that the Location Quotient (LQ) value was relatively stable and consistent in 2020 (LQ value> 1), namely the agriculture, forestry and fisheries sub-sectors (3, 30), mining and quarrying sub-sector (6.64), provision of accommodation and food and drink (1.47), government administration, defense and compulsory social security (2.00), educational services (1.38), and other services ( 1.15).